Pharmacokinetics and safety of oseltamivir in patients with end‐stage renal disease treated with automated peritoneal dialysis. (April 2015) - Patel, Kashyap; Rayner, Craig R.; Giraudon, Mylène; Kamal, Mohamed A.; Morcos, Peter N.; Robson, Richard; Kirkpatrick, Carl M.
Abstract : Aims: Patients with end‐stage renal disease (ESRD) are at increased risk of developing complications associated with influenza infection. Oseltamivir is indicated for influenza treatment in ESRD patients, but the disposition is poorly understood in this patient population. This study aimed to characterize the pharmacokinetics and tolerability of oseltamivir in automated peritoneal dialysis (APD) and construct a pharmacokinetic model to assist with optimized dosing. Methods: Ten adults with ESRD were prescribed an aggressive APD regimen consisting of three continuous cycler‐assisted peritoneal dialysis (CCPD) sessions during the day and two continuous ambulatory (CAPD) sessions overnight. Oseltamivir was administered as a single 75 mg dose, immediately before APD treatment. Results: Oseltamivir was rapidly eliminated via first‐pass metabolism, with most of the dose (Fraction metabolized = 0.964) reaching the circulation as the active metabolite, oseltamivir carboxylate. This metabolite was cleared slowly and was quantifiable throughout the sampling interval. The disposition of oseltamivir and oseltamivir carboxylate was described by a two‐ and a one‐compartment model, respectively. Metabolite clearance by CCPD [0.32 l h −1 (70 kg) −1 ] was 1.9‐fold faster than via CAPD [0.17 l h −1 (70 kg) −1 ], with renal elimination being dominant in patients with residual urine production. Model simulations showed that a single 75 mg dose attained target exposures in patients with negligible or low urine clearance. However, higher doses are recommended for further investigation in patients with high residual renal function. In all patients, oseltamivir was well tolerated. Conclusions: In APD patients with anuria or low residual renal elimination, a single 75 mg dose of oseltamivir produced exposures at the upper end of the safety margin.